Evaluation of serum zonulin for use as an early predictor for gestational diabetes - Mokkala K; Tertti K; Rönnemaa T; Vahlberg T; Laitinen K (NATURE PUBLISHING GROUP, 2022)
Diet has an important role in regulating intestinal permeability and subsequently the risk for metabolic disorders. In this observational study, we examined whether serum intestinal permeability marker zonulin, could be used as a predictor for gestational diabetes mellitus (GDM). Serum zonulin concentration was measured in early pregnancy in overweight or obese pregnant women (n = 88) at risk for developing GDM. Serum zonulin was associated with higher odds of GDM (adjusted OR for 1 ng ml(-1) increase in zonulin: 1.08, 95% CI: 1.02-1.15; P = 0.009), diagnosed by a 2-h 75-g oral glucose tolerance test at late pregnancy. The optimal cutoff value was 43.3 ng ml(-1), with sensitivity of 88% (95% CI: 71-100%) and specificity of 47% (95% CI: 33-58%). The area under the ROC-curve was 0.67 (95% CI: 0.54-0.81). Our results show an association between increased earlypregnancy serum zonulin concentration and GDM, suggesting zonulin as a possible predictor for GDM.